The risk factors of type 2 diabetes in hypertensive subjects - Chen, Yingqun; Ma, Jiner; Lu, Donghui; Fang, Yefei (Frontiers in Endocrinology, 2022)
Objective Hypertension (HTN) and type 2 diabetes (T2DM) share common risk factors and usually co-occur. This study examined the relationship between HTN history and T2DM incidence in a cohort of Chinese hypertensive subjects. Methods We recruited 443 cases (T2DM and HTN) and 443 sex- and age-matched controls (HTN). The history of peak systolic blood pressure (SBP) was divided into 140-159, 160-179, and ≥ 180 mmHg, and that of peak diastolic blood pressure (DBP) was divided into 90-99, 100-109, and ≥ 110 mmHg. Multiple binary logistic regression models were used to explore the association between controlled HTN status and T2DM. Results Creatinine concentrations were higher in the cases than in the controls (P < 0.05). The HTN duration was longer in the cases than in the controls (14.7 years vs. 13.2 years; P < 0.05). Significant differences were also found in the history of peak SBP and DBP between the cases and controls (both P < 0.05). Creatinine, HTN duration, and family history of T2DM were risk factors for T2DM in hypertensive subjects, with odds ratios (95% confidence intervals) of 1.013 (1.004-1.022), 1.025 (1.003-1.047), and 5.119 (3.266-8.026), respectively. Compared with the lowest level of peak DBP, the odds ratio for T2DM at the highest level of peak DBP was 1.757 (1.074-2.969). Subgroups analyses showed that the effect of the history of peak DBP on T2DM was significantly modified by sex (P-interaction = 0.037). Conclusion The highest DBP and the longest HTN duration were both independently associated with T2DM in hypertensive subjects.